Malaria Morbidity and Its Association With Indoor Residual Spraying in Amolatar District, Uganda: A Retrospective Ecological Study Using Routine DHIS2 Data - Sam Orech; Charles Okolimong; Esther Osir; Evaline Ajwang; David Okia (Health Science Reports, 2026)
ABSTRACT Background and Aims Despite sustained investments in malaria control, Uganda continues to experience recurrent malaria morbidity. Indoor residual spraying (IRS) is a key vector control intervention; however, evidence regarding its short‐term effectiveness under routine district‐level data remains limited. This study assessed malaria morbidity and its association with IRS in Amolatar district using routine district health information system 2 data (DHIS2). Methods A retrospective ecological observational study was conducted using monthly aggregated malaria surveillance data from all 13 public health facilities in Amolatar District between December 2024 and November 2025. Malaria data were extracted from the District Health Information System together with outpatient, laboratory, and indoor residual spraying operational records. The 12‐month dataset was used to describe annual malaria trends, while the pre–post analysis evaluated changes in malaria indicators before and after IRS implementation. The pre‐IRS period was defined as May–August 2025 ( n = 4 months), and the post‐IRS period as September–November 2025 ( n = 3 months), with IRS implemented in September 2025. A complete census of eligible records was undertaken and no sampling was performed. Malaria indicators analyzed included outpatient department (OPD) attendance, the number of patients tested, confirmed malaria cases, and test positivity rate (TPR). Differences between the pre‐ and post‐intervention periods were analyzed using paired t‐tests or Wilcoxon signed‐rank tests. Effect estimates with corresponding 95% confidence were reported. All statistical tests were two‐sided, with statistical significance set at p < 0.05. Results A total of 167,123 OPD visits were recorded during the study period, of which 123,994 individuals were tested for malaria and 44,378 were confirmed positive. Malaria transmission peaked between May and August 2025. Following IRS implementation, the mean monthly TPR declined significantly from 36% before IRS to 31.7%, representing an 11.1% relative reduction (mean difference–4.0 percentage points; 95% CI –8.4 to – 0.1; p = 0.046). No statistical significant differences were observed in outpatient attendance, number of malaria tested or confirmed malaria cases. Conclusion IRS implementation was associated with a short‐term reduction in malaria test positivity rate. Continued implementation and longer‐term analyzes using robust longitudinal analytical approaches are recommended to better understand sustained impact of indoor residual spraying on malaria morbidity.